Characterization of Airborne Microplastics Particles on Urban Roads: Types, Sizes, and Total Particles - Wati, Mimin Setia; Akas Yekti Pulih; Zamzam, Maki; Wikurendra, Edza Aria (JURNAL KESEHATAN LINGKUNGAN, 2025)
Introduction: Airborne microplastics are part of air pollution that can enter the body orally, through direct contact with the skin and inhalation. Microplastic pollution raises concerns about health and environmental impacts, especially in urban areas with high activity. This study aims to characterize microplastic particles suspended in the air on urban roads by identifying the type, size, and total number of particles. Methods: Sampling method was carried out systematically in four strategic locations with high traffic levels. Laboratory analysis using a combination of spectroscopy and optical microscopy techniques were carried out to identify the type of polymer contained in the particles and to measure the particle size distribution in detail. Results and Discussion: This study identified a total of 223 airborne microplastic particles across four urban sites, dominated by fiber types (>80%), likely from synthetic textiles. Particle sizes ranged from 0.2 mm to 4.8 mm, with Small Microplastics (<1 mm) comprising over 60% and posing potential respiratory health risks. The highest concentration was found at Point 2 (63 particles), influenced by high traffic and nearby industry. Conclusion: Microplastics, which are predominantly in the form of fibers, especially small (<1 mm) in size, which are easily dispersed by the wind and have the potential to endanger health through inhalation, are thought to come from tire friction and industrial and household activities.